Paleomagnetism of Selected Devonian Age Plutons from Maine, Vermont and New York - Miller, John D.; Kent, Dennis V. (1989)
In order to better define the Devonian paleolatitude and cratonic pole position of North America, eight Devonian plutons were studied: the Black Mountain Granite (and associated rocks) from southern Vermont, the Hartland, Lexington, Center Pond, Chain of Ponds, Pleasant Lake, and Horserace units from Maine, and the Peekskill Granite located in southeastern New York. Of the eight units, the best results come from the Peekskill Granite of New York (age ~360Ma) and the Pleasant Lake Granite of Maine (age ~400Ma) . The Peekskill yields a pole position of 117°E, 23°N, a 95 = 16° . This pole is identical to the pole from the earliest Carboniferous Deer Lake Formation from western Newfoundland, suggesting that the Peekskill Pluton has not suffered post emplacement rotation. However, the pole position is insufficiently precise to distinguish between rotation of one or both limbs of the Pennsylvania salient with respect to the craton in the Alleghanian orogeny or to evaluate the hypothesis that some portion of Newfoundland was offset from North America in the upper Devonian. Results from the Early Devonian Pleasant Lake Granite from Maine record a potentially Early Devonian magnetization with a pole position of 95°E, 2°N, a 95 = 17°. This magnetization suggests a paleolatitude of 42°S for the central Appalachians, consistent with results from the Early Devonian Andreas redbeds and so with the hypothesis that the Acadian orogeny resulted from collision of North and South America.